The German Socio-Economic Panel as Reference Data Set - Thomas Siedler; Jürgen Schupp; C. Katharina Spiess; Gert G. Wagner (Rat für Sozial- und Wirtschaftsdaten (RatSWD), 2008)
This paper discusses how household panels in general?and the German Socio- Economic Panel (SOEP) in particular?can serve as reference data for researchers collecting datasets that do not represent the full universe of the population of interest (e.g., through clinical trials, intervention studies, laboratory and behavioural experiments, and cohort studies). We first discuss potential benefits of using questions similar to those in the SOEP for studies where researchers are interested in using the SOEP as reference data. We present a comprehensive list of SOEP core questions that we recommend researchers to consider when collecting their own data. We focus on seven topics: (1) demographic and parental characteristics; (2) labour market; (3) health; (4) personality, preferences, and subjective orientations; (5) subjective wellbeing; (6) political involvement and participation, and finally, a set of core questions for young children before they enter school. Of course the selection of a minimum set of questions depends on the research question. In this paper, we offer general advice for the selection of variables to researchers interested in comparing their own data with the SOEP.
Keywords: C81; C9; I11; I3; 330; clinical trials; intervention studies; behavioural experiments; cohort studies; household panels; SOEP; reference data